(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This study delves into the intricacies and evolution of maintenance laws in India, with a focus on Section 125 of the Criminal Procedure Code (CrPC) and its interplay with personal laws. The paper examines the emergence and legal challenges of live-in relationships in the context of maintenance claims, exploring how Indian courts have adapted to societal changes. It also scrutinizes the gender-specific nature of Section 125 CrPC, debating its constitutional validity and the calls for making it gender-neutral. Furthermore, the study contrasts the secular approach of the CrPC with the provisions under Hindu and Muslim personal laws, highlighting the judicial trends in maintenance cases and the courts’ interpretation of these laws in the light of gender equality and social justice. This comprehensive analysis aims to understand whether the personal laws in India align with the gender-neutrality concept and how courts have interpreted these laws to uphold justice and welfare.